Private Sector Healthcare Investment in Indonesia: Leveraging Australia-Indonesia Partnerships for Health System Transformation - Neuhaus, Susan Josephine (Journal of Indonesian Health Policy and Administration, 2026)
Australia and Indonesia are strategic partners with expanding bilateral trade valued at AUD 26.7 billion (2022-23). Health care partnerships between the two countries offer significant opportunities for private sector engagement. Indonesia’s large population, rapidly growing middle class, and implementation of Universal Health Coverage (UHC) through the Jaminan Kesehatan Nasional (JKN) present partnership opportunities to strengthen health system capacity, address infrastructure gaps and workforce shortages, and contribute to shared economic and prosperity goals. This study explores how Australian private healthcare investment can complement government initiatives in supporting Indonesia’s UHC while advancing Australia’s regional engagement. A descriptive qualitative analysis was conducted using Indonesian and Australian government documents, Indonesia–Australia Comprehensive Economic Partnership Agreement (IA-CEPA), Katalis Program materials, peer-reviewed literatures from Google Scholar and PubMed, industry reports (EY, Oliver Wyman, and the World Bank), and publications from international organizations (WHO, ASEAN, and OECD). The study focused on four domains: hospital infrastructure, workforce development, aged care, and digital health innovation. The study identified key investment opportunities in hospital infrastructure, workforce development, aged care, supply chain resilience, and digital health innovation. Public–private partnerships (PPP), such as Aspen Medical’s “green hospital” in Depok and Icon Group’s Bali investment, demonstrate viable case studies. The IA-CEPA provides a framework for investment, workforce mobility, and technology transfer. Strategic Australian engagement offers viable pathways to strengthen Indonesia’s health infrastructure, ease pressure on public systems and the JKN deficit burden, and advance regional health equity through coordinated, capacity-building partnerships.